LAJU DEKOMPOSISI SPESIES TANAMAN PENGAKUMULASI KALSIUM (CA) TINGGI DAN RENDAH DI DAERAH HUTAN HUJAN TROPIS SUPER BASAH PADANG SUMATRA BARAT - Hermansah Hermansah; Burhanudin Burhanudin; Sri Muhara (Jurusan Tanah Fakultas Pertanian Universitas Andalas, 2010)
Study on decomposition rate of accumulating and excluder tree species of calsium (Ca) was conducted in a super wet tropical rain forest in Gadut Mountain Padang West Sumatra. The purposes of the study were : (1) to understand the rate of decomposition of biomass of Ca accumulating and excluder tree species, (2) to understand the effect of slope position (ridge, midle and lower slope) on decomposition rate within the study plot and (3) to understand the amount of nutrient release to soil ecosystem within certain period. The result of this study showed that the higher decompoisition rate among two species was Eugenia sp, as Ca accumlating tree species which grew at lower slope. Six months after decomposition, 1 ton dry biomass of Eugenia sp contributed 6,8 kg N, 0,4 kg P, 4,12 kg K, 38,76 kg Ca, and 2,1 kg Mg in to the soil. This amount might keep an equilibrium of soil nutreint balance to support the forest ecosystem. However, for one ton dry mass of Lithocarpus korthalsii sp as Ca exluder tree species, after 6 months decomposition, contributed 9,4 kg N, 1,1 kg P, 4,61 kg K, 3,76 kg Ca and 0,54 kg Mg. This indicates that Ca acumulating tree species contributed more Ca compared to Ca excluder tree species in this forest ecosystem. Keywords: Accumulating tree sp., exluder tree sp., decomposition rate, super wet and tropical rain forest.